Hubungan antara Keadilan Organisasi dengan Keterikatan Kerja pada PT.X Surabaya (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2020)
The purpose of this study was to determine the relationship between organizational justice and work engagement at PT.X Surabaya. The total subjects in this study were 86 employees. This type of research that will be used is a quantitative approach with saturation sampling techniques. The hypothesis proposed in this study is that there is a positive relationship between organizational justice and work engagement. The measuring instrument used in this study is Utrecht Work The Engagement Scale (UWES) developed by Schaufeli and Bakker (2003) totaled 17 items and The Scale of organizational justice developed by Neihoff and Moorman (1993) totaled 20 items.correlation results Product Moment show the value of the correlation coefficient rxy = 0.489 p = 0,000 (p <0.01) which means there is a significant positive relationship between organizational justice with work engagement. The higher the level of organizational justice, the higher the level of work engagement that employees have, conversely the lower the level of organizational justice, the lower the work engagement that employees have. Keywords: Work Engagement, Organizational Justice, Faculty Of Psychology